New Wave of Accreditation in Indian Higher Education : Comparison of Accreditation Bodies for Management Programmes - Bagga, Teena; Bansal, Sanjeev; Kumar, Pradeep; Jain, Sanchit (Prabandhan: Indian Journal of Management, 2016)
The Indian educational system is witnessing yet another major shift. Currently, more and more higher educational institutes are going for national and international accreditations. The accreditation process helps educational institutes in achieving augmented academic quality by benchmarking, and also enable students and various other stakeholders to be informed of choices with regard to institutions. Some institutions are already accredited; some are in the process, but majority are in the thinking phase. This paper presented a comprehensive comparison of some of the most respected international accreditation bodies like AACSB (Association to Advance Collegiate Schools of Business) - USA ; AMBA (Association of MBAs) - UK ; EQUIS (EFMD Quality Improvement System) - EU ; IACBE (International Assembly for Collegiate Business Education) - USA ; and also the major Indian accreditation bodies, NBA (National Board of Accreditation) and NAAC (National Assessment&Accreditation Council). This comparison is a ready reckoner to have an understanding of various management accreditation boards in terms of eligibility, duration of accreditation, criteria, and so forth.